(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Proniosomal gel formulations of miconazole nitrate (MCZ) were prepared by using combinations of different grades of (non-ionic surfactant) span, cholesterol, and lecithin by coacervation phase separation method. Developed 10 proniosomal gel formulations were characterized for particle size, shape, % entrapment efficiency, drug content, in vitro drug permeation, scanning electron microscopy (SEM), DSC, stability study. The fourier transform infrared spectroscopy (FTIR) studies confirmed the compatibility of the drug with excipients. The results showed that all the formulations were pale yellow to pale brown in color, pH was is in the range of 5.60 to 7.20, and encapsulation efficiency was found is in the range of 83 to 91.25% and particle size in between 5.81 ± 0.2 to 07.52 ± 0.07. Among the ten formulations MF2, MF3, MF5, MF6, and MF8 showed maximum drug release in a controlled manner at 12 hours of study and developed into carbopol proniosomal topical gel and evaluated for ex-vivo drug permeation. Formulation-optimized formulation C5MF8 showed higher drug permeation 74.19 ± 0.16% at 12 hr. with a flux value of 6.829 ± 0.12 μg/cm2/hr. The permeability coefficient of 0.341 ±0.08 cm2/hrs., higher correlation coefficient R2 0.9944 for zero-order drug release kinetic model, and follows zero-order release kinetics. Among the 5 formulations, optimized carbopol proniosomal topical gel formulation C5MF8 drug release and in-vitro antifungal activity was compared with marketed formulation cream.C5MF8 showed sustain drug release and zone of inhibition value was very near to marketed preparation. Hence it was concluded that developed carbopol proniosomal topical gel had the potential to act as a controlled release drug carrier, which sustains the drug release for many hours and exhibit good antifungal activity.